Communicative indicators of context advertising in the digital marketing system - Зінюк, А. В.; Каторов, Д. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
Features of the development of communication technologies give users considerable freedom. They can find the same product on different sites, go online using multiple devices. Therefore, it is no longer enough to use one channel, one message or one device for a successful and effective advertising campaign. It is necessary to build a holistic system of traffic sources, which will consist of several successive stages. The article discusses contextual advertising for the search and content network. Search advertising is used for additional (auxiliary) or final contact before conversion. It becomes ancillary if the purchase cycle is quite long, and the customer does not immediately make a purchase decision. Final - if the purchase cycle is short, or the user is in the last stage of this cycle. Remarketing should be used to get your audience back to your site. The technology allows you to show ads to users who have already visited the site. Thus, remarketing becomes the last channel before the conversion. The authors emphasize that it is possible to optimize multichannel attribution through key indicators of communicative efficiency: involvement, interaction and conversion. The main indicators of engagement are indicators that indicate the user's attitude to advertising (indicator of ad quality, impressions and views, clicks). Interaction indicators indicate how the user behaved on the site after going to the ad (time spent on the site, the rate of output and depth of viewing the site). The last level of indicators has the greatest value, because it indicates the direct effectiveness of advertising, which is mainly expressed in financial equivalent (customer costs and return on investment).